Optimization of the Role and Function of Ward Manager in the Development of the Family Meeting Innovation Program in the Intensive Care Unit - Arhamsyah Arhamsyah; Krisna Yetti; Tuti Afriani; Dyah Fitri Wulandari (Indonesian Journal of Global Health Research, 2025)
Hospitalization in the ICU has an impact on families, making it essential to meet the needs of families in the care of patients in the ICU. Caring for patients in the Intensive Care Unit (ICU) requires family support and involves various health disciplines, including the active role of the head nurse. The head nurse can facilitate all parties to be involved in patient management, one of which is through family meetings. (family meeting). A family meeting is an important forum to discuss the patient's condition, prognosis, and care preferences, to listen to the family's concerns, and to make decisions about appropriate treatment goals. Objective to enhance family satisfaction in patient care in the ICU through the development of an innovative family meeting program. Using the case report method in managing care in the ICU through stages of data collection, problem identification, discussion, and determining alternative solutions. Utilizing fishbone analysis to find the root cause of the problem. Once the problem is identified, the next steps include prioritizing the issues, developing a plan of action, implementing it, and conducting evaluations along with follow-up plans. The development of the family meeting innovation program with the establishment of guidelines for the implementation of family meetings, Standard Operating Procedures (SOP), and documentation formats for family meetings. The implementation of family meetings serves as a programmed communication medium between families and caregiving professionals, thereby enhancing the satisfaction of patient families.